1991
DOI: 10.1161/01.cir.84.2.896
|View full text |Cite
|
Sign up to set email alerts
|

Improved blood flow during prolonged cardiopulmonary resuscitation with 30% duty cycle in infant pigs.

Abstract: Background. Sustained compression is recommended to maximize myocardial and cerebral blood flow during cardiopulmonary resuscitation (CPR) in adults and children. We compared myocardial and cerebral perfusion during CPR in three groups of 2-week-old anesthetized swine using compression rates and duty cycles (duration of compression/total cycle time) of 100 per minute, 60%; 100 per minute, 30%; and 150 per minute, 30%1.Methods and Results. Ventricular fibrillation was induced and CPR was begun immediately with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

1994
1994
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 26 publications
0
24
0
2
Order By: Relevance
“…A further study in piglets suggested that sustained chest compressions had a deleterious effect on myocardial and cerebral perfusion, especially during prolonged resuscitation. 76 A physiologic mathematical modeling study suggested that using higher compression-ventilation ratios would result in underventilation of asphyxiated infants (LOE 5 77 ). The model predicts that between 3 and 5 compressions to 1 ventilation should be most efficient for newborns.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…A further study in piglets suggested that sustained chest compressions had a deleterious effect on myocardial and cerebral perfusion, especially during prolonged resuscitation. 76 A physiologic mathematical modeling study suggested that using higher compression-ventilation ratios would result in underventilation of asphyxiated infants (LOE 5 77 ). The model predicts that between 3 and 5 compressions to 1 ventilation should be most efficient for newborns.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Consequently, the evidence base for these interventions during neonatal resuscitation remains low, and data is extrapolated largely from adult or animal resuscitation studies (1,7,8). However, most animal studies have been conducted in adult models (10,11) or newborn animals (12)(13)(14) that were hours or days into postnatal life. Therefore, most of the information from these studies is of limited applicability to neonatal delivery room resuscitation.…”
mentioning
confidence: 99%
“…The dyssynchrony also could increase the duty cycle. Animal studies have shown that 30% of compression duty cycle provides superior coronary and cerebral perfusion compared with 60% of duty cycle [24,25]. Under the consideration of practical and educational feasibility, guidelines suggest the optimal level to be a 50% of duty cycle [2].…”
Section: Discussionmentioning
confidence: 99%